The effect of cross-linking procedure on corneal wavefront aberrations in patients with keratoconus - Resan, Mirko; Cvejić, Željka; Baenninger, Philipp; Hafezi, Farhad; Massa, Horace; Vukosavljević, Miroslav; Pajić, Bojan (Vojnosanitetski pregled, 2022)
Background/Aim. Corneal cross-linking (CXL) treatment shows the best results in stabilizing the cornea and stopping the progress of the ectatic process. The aim of the study was to assess the impact of CXL on the keratoconus regarding higher-order aberrations (HOAs) and potential improvement of visual function. Methods. In 19 patients, a standard epithelium-off CXL was performed with an energy density of three mW/cm2 for half an hour. The cornea was examined by Pentacam topography before CXL and one and six months after CXL. Best-corrected visual acuity (BCVA), topographic data, and aberrations were collected. Results. A significant reduction in vertical coma was observed from preoperative -1.03 ± 1.89 to -0.74 ± 1.73 (p = 0.004) six months after CXL, and in spherical aberration from preoperative -0.22 ± 1.05 to -0.08 ± 1.13 (p = 0.002) six months after CXL. Root mean square (RMS) HOAs six months after CXL also significantly reduced from 2.31 ± 1.82 to 2.26 ± 1.84 six months after CXL (p = 0.001). BCVA improved from preoperative 0.43 ± 0.15 to 0.71 ± 0.19 six months after surgery (p < 0.001). Conclusion. CXL is a very potent treatment method for keratoconus, which significantly reduces certain corneal wavefront aberrations, especially vertical coma, spherical aberration, and RMS, and leads to a significant improvement in visual acuity.